Phenotypic evaluation of gamma-induced dwarf mutants in Dendrobium crumenatum at M2 generation - RINDANG DWIYANI; IDA AYU PUTRI DARMAWATI; RETNO KAWURI; YUYUN FITRIANI; RINI HERMINA KAMUHI; WAFA’ NUR HANIFAH; I PUTU BENNY SANTIKA (Asian Journal of Agriculture, 2026)
Abstract. Dwiyani R, Darmawati IAP, Kawuri R, Fitriani Y, Kamuhi RH, Hanifah WN, Santika IPB. 2026. Phenotypic evaluation of gamma-induced dwarf mutants in Dendrobium crumenatum at M2 generation. Asian J Agric 10 (1): g100150. https://doi.org/10.13057/asianjagric/g100150. Bali, Indonesia, has strong potential for the development of ornamental orchids, particularly compact cultivars with high commercial value. Dendrobium crumenatum, a native Indonesian orchid, is widely appreciated for its white, fragrant flowers; however, its tall growth habit limits its suitability as a potted ornamental plant. This study aimed to induce and evaluate dwarf phenotypes in D. crumenatum using gamma irradiation. Plantlets were exposed to 0, 5, 10, 15, and 20 Gy, arranged in a completely randomized design with five replicates and three plantlets per replicate (n=75). Morphological traits were assessed after in vitro culture and acclimatization. Data were analyzed using analysis of variance followed by the Least Significant Difference (LSD) test at a 5% significance level (p<0.05). Gamma irradiation significantly affected all measured traits. The 5 Gy treatment caused severe growth suppression, reducing plant height, leaf number, and shoot number by approximately 53.7%, 81.7%, and 84.4%, respectively, compared to the control. In contrast, the 10 Gy treatment achieved a similar reduction in plant height (~52.6%) while maintaining higher leaf number (~83.3% of control) and shoot number (~62.2% of control), indicating a more balanced morphological response. The 15 Gy treatment showed minimal deviation from the control, whereas 20 Gy produced semi-compact plants with moderate shoot retention. These results demonstrate a non-linear dose-response relationship, where intermediate doses (particularly 10 Gy) optimize the trade-off between dwarfism and vegetative performance. These findings indicate that medium gamma irradiation doses are effective for generating dwarf D. crumenatum mutants suitable for potted ornamental use and demonstrate the potential of mutation breeding to support orchid improvement and the floriculture industry.